The gender perspective for a changing city. Time, Space and Covid in Milan - Francesca Zajczyk (Academicus, 2021)
The city has become a space of diversity. To be sustainable, inclusive and less unequal, urban policy and policies must therefore take these differences into account. In this moving film, the female component represents a fundamental aspect. For a heavy cultural question, in Italy there has been a delay in society with respect to the idea of equal opportunities between men and women. Italy remains far from the watchword - mainstreaming - which Europe, on the other hand, has begun to develop and disseminate. And it is a European document that for the first time introduces the theme of the “right to the city for women”. There is certainly no shortage of innovative cases also promoted by female figures in Italian local administrations. In practice, however, a systematic overview is lacking. Apart from the issue of sustainable mobility, temporal policies are particularly important for a gender sensitive territorial planning. The interesting and innovative aspect is the transversality of the temporal dimension, both in the lives of individuals and in the social organization of urban space. The lockdown canceled the diversification of the times of daily life and the use of urban space: “time” considered a certain fact, never questioned, has become a precious, quality asset; through new rhythms for a new urban livability and mostly for a better life of women. For this to happen, however, the city must change its skin, it must change its thinking and above all its rhythms. And this is precisely the perspective recalled in a document drawn up by the Municipality of Milan: “Milan 2020 - Adaptation strategy” (Municipality of Milan, 2020). Therefore, a new Territorial Schedule Plan, whose specificity is the transversality of the temporal dimension. A new city management tool through the organization of time, from timetables to accessibility with particolar attention to the prospect of a “city 15 minutes away”. Promoting women’s well-being satisfies collective and community interests and improves the quality of all: women and men.